Rhetorical Strategies in Late Antique Literature : Images, Metatexts and Interpretation - Quiroga Puertas, Alberto J. (Mnemosyne, Supplements, Late Antique Literature Ser, 2017)
‎Contents -- ‎Acknowledgements -- ‎Introduction (Van Hoof) -- ‎Chapter 1. "I Also Have to Dialogue with the Posterity". Aelius Aristides' Legacy to the Late Antiquity (Miletti) -- ‎Chapter 2. ‭Σωφροσύνη‬ and Self-Knowledge in Methodius' Symposium (Fowler) -- ‎Chapter 3. Rhétorique et argumentation dans l'Apologétique latine de la période constantinienne (Lopetegui Semperena) -- ‎Chapter 4. Image and Word in Eusebius of Caesarea (VC 3.4-24): Constantine in Nicaea (Torres Guerra) -- ‎Chapter 5. In Heaven unlike on Earth. Rhetorical Strategies in Julian's Caesars (Quiroga Puertas) -- ‎Chapter 6. Asianism, Arianism, and the Encomium of Athanasius by Gregory of Nazianzus (MacDougall) -- ‎Chapter 7. Rhetoric against the Theatre and Theatre by Means of Rhetoric in John Chrysostom (Lugaresi) -- ‎Chapter 8. Socrates amongst the Holy Men. Socratic Paradigms and Styles in Eunapius' Lives (Campos Daroca) -- ‎Chapter 9. Harmonia's Necklace (Nonn. D. 5.135-189): A Set of Jewellery, ekphrasis and a Narrative Node (Miguélez-Cavero) -- ‎Bibliography -- ‎Index of Names and Terms.